Reflexes of the Pandemic in school dropout/exit: the democratization of access and permanence - Celestina Maria Pereira de Souza; Jhonata Moreira Pereira; Maria da Conceição de Jesus Ranke (Universidade Federal do Norte do Tocantins, 2020)
The study focuses on educational policies, focusing on the National Education Plan (PNE / 2014) and the State Education Plan (PEE/2015) of the State of Tocantins. This is a bibliographic research, through the trajectory of the process of elaborating the PNE / 2014 and the subnational plans, emphasizing the conditions of preparation, monitoring and evaluation, and publicizing the results achieved. The objective of the investigation is to analyze the results of the State of Tocantins, based on the reports published by PNE/2014. In view of the analysis, it is possible to state that the process of monitoring and evaluating the evolution of the goals proposed in the PEE/2015 compromised by the failure to comply with the planned steps. Thus, the investigation goes back to some repercussions, demonstrating that the dropout / dropout rates of students became more manifest between the initial period and the present moment of the pandemic. Covid-19 is an aggravating factor in school dropout, highlighting the need for coping actions to combat it, especially in this context of uncertainty and in view of the impacts of the pandemic on education.